Keputusan Bisnis: Teknologi Artificial Intelligence dan Strategi Bisnis - Wirataman, Muhammad Jaka; Fitri, Aida; Harbiyah G, Harbiyah G (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
Artificial Intelligence technology and strategy play an important role in business decision making. However, technology and business strategy have a very important influence on business actors in making decisions. The purpose of this quantitative study is to determine the impact of artificial intelligence technology and business strategy on business decisions in Banda Aceh. The method used in this study is a quantitative method that aims to determine the influence or relationship between two or more variables in a study. This study involved 96 respondents spread across Banda Aceh City. Based on respondents who decided to do business and researchers using a random sampling method. Research data were collected through a list of questions/questionnaires and documentation studies. Hypothesis testing using multiple linear regression analysis, F test (simultaneous) and t test (partial) is intended to determine the effect of independent variables on dependent variables at a 95% confidence level (α = 0.05). The results of the study indicate that artificial intelligence technology has a strong influence on business decisions, and business strategies have a close influence on business decisions. If combined simultaneously there is a significant contribution to business decisions in Banda Aceh City, with a contribution of 288.670% of its variance. This study can not only be used for ongoing business actors but also for novice business actors significantly. So, the implication in this study is that artificial intelligence and strategy can influence business decisions in Banda Aceh.